High-Performance-Based Perovskite-Supported Nanocomposite for the Development of Green Energy Device Applications: An Overview - Chen, Tse-Wei (Nanomaterials (Basel), 2021)
Perovskite-based electrode catalysts are the most promising potential candidate that could bring about remarkable scientific advances in widespread renewable energy-storage devices, especially supercapacitors, batteries, fuel cells, solid oxide fuel cells, and solar-cell applications. This review demonstrated that perovskite composites are used as advanced electrode materials for efficient energy-storage-device development with different working principles and various available electrochemical technologies. Research efforts on increasing energy-storage efficiency, a wide range of electro-active constituents, and a longer lifetime of the various perovskite materials are discussed in this review. Furthermore, this review describes the prospects, widespread available materials, properties, synthesis strategies, uses of perovskite-supported materials, and our views on future perspectives of high-performance, next-generation sustainable-energy technology.